Faktor-Faktor yang Berhubungan dengan Persalinan Prematur di RSUD Buleleng - Ni Ketut Henny Swasti Aryani (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2025)
Preterm birth, defined as delivery before 37 completed weeks of gestation, is one of the leading causes of neonatal morbidity and mortality worldwide. This condition can be influenced by various factors, including obstetric and sociodemographic factors. This study aimed to identify the factors associated with preterm birth at the Regional Public Hospital (RSUD) of Buleleng Regency. A case-control study design with a retrospective approach was employed from January to March 2025. The accessible population included all preterm births at RSUD Buleleng from January to December 2024. A total of 268 respondents (134 cases and 134 controls) were selected using simple random sampling. The results showed significant associations between maternal age and preterm birth (p < 0.001; AOR 6.565; 95% CI 3.119-13.817), employment status (p = 0.007), parity (p = 0.002), premature rupture of membranes (p < 0.001; AOR 6.207; 95% CI 2.123 – 18.148), and threatened preterm labor (p < 0.001; AOR 4.150; 95% CI 2.137 – 8.059). No significant association was found between educational level or history of preeclampsia and preterm birth. Maternal age was identified as the most dominant predictor. These findings highlight the importance of early detection by healthcare providers to prevent preterm birth and its associated complications.